Unfolding the Role of Non-State Actors in Rohingya Refugee Crisis at Bangladesh - A N M Zakir HOSSAIN (Košická bezpečnostná revue, 2020)
The figure of refugees has amplified significantly because of armed conflicts in several parts of the world. The refugee issue has been a sensitive subject for states because states that cause refugee problems are perceived as those that are intolerant of racial, religious or linguistic minorities. Rohingya are facing an uncertain future with a lot of violations and vulnerabilities that ultimately made them stateless and put in an identity crisis. The present study focuses on the nexus between non-state actors and refugee management which shaped the refugee crisis management architecture in Bangladesh. The study aimed to identify the role of non-state actors to manage the crisis. The study endeavours to answer the questions on how non-state actors and refugees act and react with each other in this crisis and how it indicates the future role of state actors in refugee management and resettlement. The study is primarily based on secondary sources of data to reach the inferences. The research study examined an array of non-state institutions that impact on humanitarian and resettlement of Rohingya refugees. It is evident that non-state actors create a platform that embraces the different stakeholders and emphasized the trade-off between them. The study concludes by arguing for local, regional, and global incentives required for their resettlement in the future because there is a lack of policy to make up the resettlement of refugees.